PENGARUH PEMBIAYAAN MUDHARABAH DAN MUSYARAKAH TERHADAP KINERJA KEUANGAN PADA PT. BANK MUAMALAT INDONESIA TAHUN 2018-2025 - Yodi Pranata; Ahmad Syahrizal; Rohana (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to examine the effect of mudharabah and musyarakah financing on financial performance, proxied by Return on Assets (ROA), at PT Bank Muamalat Indonesia Tbk during the 2018–2025 period. This research employed an associative quantitative approach using secondary data obtained from quarterly financial reports. The sample consisted of 32 observations selected through purposive sampling. Data were analyzed using multiple linear regression with the assistance of IBM SPSS Statistics version 27. The findings indicate that mudharabah financing has no significant effect on ROA, as evidenced by a significance value of 0.414 and a t-value of 0.829. Similarly, musyarakah financing does not significantly affect ROA, with a significance value of 0.079 and a t-value of 1.819. Simultaneously, both financing variables also show no significant effect on ROA, indicated by an F-value of 2.507 and a significance value of 0.128. These results suggest that the relationship between profit-sharing financing and the profitability of Islamic banks remains complex and may be influenced by other factors beyond the variables examined in this study.